(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The literature of the Middle Ages (V-XV centuries) and the Renaissance (XIV-XVII centuries) played an important role in the development of Western and Eastern cultures. There are many distinctive features, themes and styles in the literature of these periods, which when compared with each other produce interesting results. This article analyzes the main features, themes and styles in Western and Eastern literature of the Middle Ages and the Renaissance.